2015
DOI: 10.1063/1.4919683
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics and chemical bonding in Sb2Te3 from first-principles calculations

Abstract: Pressure effects on the lattice dynamics and the chemical bonding of the three-dimensional topological insulator, Sb2Te3, have been studied from a first-principles perspective in its rhombohedral phase. Where it is possible to compare, theory agrees with most of the measured phonon dispersions. We find that the inclusion of relativistic effects, in terms of the spin-orbit interaction, affects the vibrational features to some extend and creates large fluctuations on phonon density of state in high frequency zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Wang et al observed imaginary frequencies in the calculated phonon spectra of relaxed Bi 2 Te 3 and Bi 2 Se 3 with LDA+SOI. Later, the same group found that the imaginary frequencies could be eliminated by adopting a larger supercell in the “frozen phonon” procedure, exemplified by the result of Sb 2 Te 3 . Chen et al reported that LDA provides a better description of phonon dispersions in Bi 2 Te 3 compared with the PBE calculations.…”
Section: Phonon Dispersion and Lattice Thermal Conductivity Of (Bi1–xmentioning
confidence: 99%
“…Wang et al observed imaginary frequencies in the calculated phonon spectra of relaxed Bi 2 Te 3 and Bi 2 Se 3 with LDA+SOI. Later, the same group found that the imaginary frequencies could be eliminated by adopting a larger supercell in the “frozen phonon” procedure, exemplified by the result of Sb 2 Te 3 . Chen et al reported that LDA provides a better description of phonon dispersions in Bi 2 Te 3 compared with the PBE calculations.…”
Section: Phonon Dispersion and Lattice Thermal Conductivity Of (Bi1–xmentioning
confidence: 99%
“…Such an approach has been widely used in the literatures [24,25,26]. In fact, it was previously shown that SOC has minor effects in the geometry optimization and phonon calculations [27,28].…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of the vdW dispersion corrections gives a much better agreement with the experimental values and, in this case, the two lattice parameters a and c are overestimated and underestimated by approximately 0.7%, respectively. The importance of the long-range dispersive interactions in predicting ground states and describing the interlayer distance in different classes of materials has long been recognized [66][67][68][69][70].…”
Section: A Bulk Propertiesmentioning
confidence: 99%